Size matters: computational insights into the crowning of noble gas trioxides - Dash, Soumya Ranjan; Sharma, Himanshu; Tiwari, Mrityunjay K.; Greb, Lutz; Vanka, Kumar (Inorganic Chemistry, 2024)
In pursuit of enhancing the stability of the highly explosive and shock-sensitive compound XeO3, we performed quantum chemical calculations to investigate its possible complexation with electron-rich crown ethers, including 9-crown-3, 12-crown-4, 15-crown-5, 18-crown-6, and 21-crown-7, as well as their thio analogues. Furthermore, we expanded our study to other noble gas trioxides (NgO(3)), namely, KrO3 and ArO3. The basis set superposition error (BSSE) corrected interaction energies for these adducts range from -13.0 kcal/mol to -48.2 kcal/mol, which is notably high for sigma-hole-mediated noncovalent interactions. The formation of these adducts was observed to be more favorable with the increase in the ring size of the crowns and less favorable while going from XeO3 to ArO3. A comprehensive analysis by various computational tools such as the mapping of the electrostatic potential (ESP), Wiberg bond indices (WBIs), Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, noncovalent interaction (NCI) plots, and energy decomposition analysis (EDA) revealed that the C-H center dot center dot center dot O interactions, as well as dispersion interactions, play a pivotal role in stabilizing adducts involving larger crowns. A noteworthy outcome of our study is the revelation of a coordination number of 9 for xenon in the complex formed between XeO3 and the thio analogue of 18-crown-6, which is higher than the largest number reported to date.